A comprehensive evaluation of the therapeutic potential of silibinin: a ray of hope in cancer treatment - Ray, Pantha Prodip; Islam, Mohammad Ashraful; Islam, Mohammad Safiqul; Han, Aixia; Geng, Peiwu; Aziz, Md. Abdul; Mamun, Abdullah Al (Frontiers in Pharmacology, 2024)
Background: Natural compounds hold promise in the search for cancer therapies due to their unique chemical structures and combinations that may effectively combat cancer while minimizing toxicity and side effects compared to conventional treatments. Silibinin, a natural lignan, has been found to possess strong anti-cancer activity against several types of human cancers based on emerging research. This study aims to provide an overview of the therapeutic potential of silibinin in the treatment and prevention of cancers.Methods: A comprehensive search was conducted using various internet databases such as PubMed, Google Scholar, and Science Direct to identify relevant research papers.Results: Silibinin has been shown to exhibit anticancer activity against several types of cancers, including liver, lungs, breast, prostate, colorectal, skin, and bladder cancers. Its multifaceted mechanisms of action contribute to its therapeutic effects. Silibinin exerts antioxidant, anti-inflammatory, anti-proliferative, pro-apoptotic, anti-metastatic, and antiangiogenic activities, making it a promising candidate for cancer therapy. One of the key mechanisms underlying silibinin's anticancer effects is its ability to modulate multiple signaling pathways involved in cancer development and progression. It can inhibit the activation of various oncogenic pathways, including PI3K/Akt, NF-κB, Wnt/β-catenin, and MAPK pathways, thereby suppressing cancer cell proliferation, inducing cell cycle arrest, and promoting apoptosis.Silibinin possesses great potential as an effective treatment agent for cancer.Silibinin holds excellent promise as a therapeutic agent in the management of cancer. Its multifaceted mechanisms of action, favorable safety profile, and potential synergistic effects with conventional therapies make it an attractive candidate for further investigation and development as a cancer treatment. However, more extensive clinical studies are necessary to fully establish its efficacy, optimal dosage, and long-term effects in cancer patients.